Securing cloud storage by applying file encryption software using AES encryption technique / Mohd Shafrul Izzuddin Mohd Saharuddin - Mohd Saharuddin, Mohd Shafrul Izzuddin (2020)
This paper reviews vulnerabilities on cloud storage from the anonymous such as MITM or DDOS Attack and the solution on how to secure the data of the user when upload to cloud storage. To answer this question, encryption is the suitable method that relevant and can be use of by applying before uploading to cloud storage. The encryption will encrypt the file before upload to the cloud storage. The results revealed that file successfully encrypt and cannot be previewed before it is decrypted. From a safety perspective, this study emphasizes the need to consider the impact of these environmental changes along with the expert’s adaptive capacities. The features also can be invented depends on the issue that happen.